Method for fabricating carbon nanomaterial-containing films

The method of using light-activated etching with an oxidant-containing etchant efficiently patterns graphene-containing films, addressing the inefficiencies of existing methods and enabling rapid production of carbon nanomaterial-based electronic devices.

JP7671057B2Active Publication Date: 2025-05-01NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021063926
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-14
Filing Date
2021-04-05
Publication Date
2025-05-01
Estimated Expiration
2041-04-05

AI Technical Summary

Technical Problem

Existing methods for patterning graphene-containing films are inefficient and require lengthy processes, making them unsuitable for rapid and scalable production of carbon nanomaterial-based electronic devices.

Method used

A method involving the formation of a resist mask or metal mask on a carbon nanomaterial-containing film, followed by irradiation with light in the presence of an etchant containing an oxidant, such as hypochlorous acid, to efficiently etch and pattern the film.

Benefits of technology

This method allows for the rapid and efficient etching of carbon nanomaterial-containing films under mild conditions, enabling the formation of patterned films suitable for electronic device applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671057000001
    Figure 0007671057000001
  • Figure 0007671057000002
    Figure 0007671057000002
  • Figure 0007671057000003
    Figure 0007671057000003
Patent Text Reader

Abstract

To provide a method for simply and rapidly etching a carbon nanomaterial-containing membrane formed on a substrate.SOLUTION: This processing method comprises: forming a resist mask and / or a metallic mask on a carbon nanomaterial-containing membrane on a substrate; irradiating the carbon nanomaterial-containing membrane with light in presence of an etchant including an oxidant; and removing the resist mask and / or the metallic mask. A carbon nanomaterial may be a carbon nanotube, graphene, or fullerene. The carbon nanomaterial-containing membrane may be single-layer graphene or a stacked membrane of graphene. The oxidant can be selected from hypochlorous acid and sodium hypochlorite. The concentration of the oxidant in the etchant may be adjusted in a range of, for example, 1 wt.% to 25 wt.%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] One embodiment of the present invention relates to a method for processing a film including a carbon nanomaterial. For example, one embodiment of the present invention relates to a method for patterning a graphene-containing film formed on a substrate by wet etching. [Background technology]

[0002] Carbon nanomaterials, such as carbon nanotubes, graphene, and fullerenes, are sp 2 Carbon nanomaterials are materials composed of carbon atoms, and due to their unique two- or three-dimensional structure, they exhibit extremely high electron mobility, electrical conductivity, thermal conductivity, and mechanical properties. For this reason, carbon nanomaterials have attracted attention as new materials to replace existing materials in various fields. By processing and patterning a film containing carbon nanomaterials, it is also possible to fabricate electronic devices that utilize the excellent electrical properties of carbon nanomaterials. For example, Patent Documents 1 and 2 and Non-Patent Documents 1 to 3 disclose a method of patterning a graphene thin film formed on a substrate by etching it. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-172792 A [Patent Document 2] JP 2013-225649 A [Non-patent literature]

[0004] [Non-Patent Document 1] Bell, DC, et al., "Precision Cutting and Patterning of Graphene with Helium Ions," Nanotechnology, (UK), 2009, Vol. 20, 455301. [Non-Patent Document 2] Cong, CX, et al., "Fabrication of Graphene Nanodisk Arrays Using Nanosphere Lithography," Journal of Physical Chemistry C, (USA), 2009, Vol. 113, p. 6529-6532 [Non-Patent Document 3] Lemme, MC, et al., "Etching of Graphene Devices with a Helium Ion Beam," ACS Nano, (USA), 2009, Vol. 9, pp. 2674-2676 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of one embodiment of the present invention is to provide a novel method for etching a film containing a carbon nanomaterial. For example, an object of one embodiment of the present invention is to provide a method for easily and quickly etching a graphene-containing film formed on a substrate. [Means for solving the problem]

[0006] One embodiment of the present invention is a method for processing a carbon nanomaterial-containing film, comprising forming a resist mask and / or a metal mask on a carbon nanomaterial-containing film on a substrate, irradiating the carbon nanomaterial-containing film with light in the presence of an etchant containing an oxidizing agent, and removing the resist mask and / or the metal mask.

[0007] The carbon nanomaterial may be selected from carbon nanotubes, graphene, and fullerene, and the carbon nanomaterial-containing film may be a single layer of graphene or a multilayer film of graphene.

[0008] The oxidizing agent can be selected from hypochlorous acid and sodium hypochlorite. The concentration of the oxidizing agent in the etchant may be adjusted within a range of, for example, 1% by weight to 25% by weight. The etchant may further contain a surfactant, the concentration of which is selected, for example, from 0.01% by weight to 10% by weight. The surfactant may be an ionic surfactant or a nonionic surfactant.

[0009] The light irradiation is performed so as to excite the oxidizing agent. For example, the light irradiation may be performed in a state where the carbon nanomaterial-containing film is immersed in the etchant. In the light irradiation, light including light having a wavelength selected from the range of 200 nm to 400 nm can be used. Effect of the Invention

[0010] According to one of the embodiments of the present invention, a carbon nano material-containing film can be etched under mild conditions in a short time, and a patterned carbon nano material-containing film can be formed. [Brief description of the drawings]

[0011] [Figure 1] 1A to 1C are schematic cross-sectional views showing a method for processing a carbon nanomaterial-containing film according to one embodiment of the present invention. [Diagram 2]2 shows optical microscope photographs of the graphene-containing film of Example 1. Fig. 2(A) is a photograph before etching, Fig. 2(B) and Fig. 2(C) are photographs after immersing in the etchant and irradiating it with light for 5 minutes and 20 minutes, respectively, and Fig. 2(D) is a photograph after leaving the graphene-containing film immersed in the etchant for 120 minutes without irradiating it with light. [Diagram 3] Figures 3(A) and 3(B) are the Raman spectra of measurement points 1 to 4 shown in Figures 2(A) and 2(B), respectively. [Figure 4] 4(A) and 4(B) are the Raman spectra of measurement points 1 to 4 shown in FIG. 2(C) and FIG. 2(D), respectively. [Diagram 5] 5A and 5B are optical microscope images of the graphene-containing film of Example 2. Fig. 5A is a photograph before etching, and Fig. 5B is a photograph after 5 minutes of light irradiation while immersed in an etchant. [Figure 6] 6(A) and 6(B) are the Raman spectra of measurement points 1 to 4 shown in FIG. 5(A) and FIG. 5(B), respectively. [Figure 7] FIG. 7(A) is an optical microscope image of the graphene-containing film before etching in Example 3, and FIG. 7(B) is a mapping diagram of 2D band peak intensity in the Raman spectrum of the dotted square region in FIG. 7(A). [Figure 8] FIG. 8(A) is an optical microscope image of the graphene-containing film after etching in Example 3, and FIG. 8(B) is a mapping diagram of 2D band peak intensity of the Raman spectrum of the dotted square region in FIG. 8(A). [Figure 9] FIG. 9(A) is a phase distribution image obtained by an atomic force microscope (AFM) of the graphene-containing film after etching in Example 3, and FIG. 9(B) is a height analysis result along the line AA′ in FIG. 9(A). [Figure 10] 1A to 1C are schematic cross-sectional views showing a method for processing a carbon nanomaterial-containing film according to one embodiment of the present invention. [Figure 11] 1A to 1C are schematic cross-sectional views showing a method for processing a carbon nanomaterial-containing film according to one embodiment of the present invention. [Figure 12]FIG. 12(A) is an optical microscope image of sample A after the formation of a metal mask in Example 4, the left image in FIG. 12(B) is an optical microscope image of sample A after etching, and the right image in FIG. 12(B) is a mapping diagram of 2D band peak intensities in the Raman spectrum of the dotted rectangular region in the left image. [Figure 13] FIG. 13(A) is an optical microscope photograph of sample A after the formation of a metal mask in Example 4, FIG. 13(B) is an optical microscope photograph of sample A after etching, and the left diagram in FIG. 13(C) is an enlarged view of the dotted rectangular portion in FIG. 13(B), and the right diagram in FIG. 13(C) is a mapping diagram of 2D band peak intensity of the Raman spectrum of the dotted rectangular region in the left diagram. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiments of the invention disclosed in this application will be described. Even if there are other effects and advantages different from those brought about by the following embodiments, those that are obvious from the description in this specification or that can be easily predicted by a person skilled in the art are naturally understood to be brought about by the present invention.

[0013] One embodiment of the present invention is a method for processing a film containing a carbon nanomaterial by etching. This processing method will be described below with reference to schematic cross-sectional views of Figures 1(A) to 1(D).

[0014] 1. Processing method flow In this processing method, first, as shown in FIG. 1(A), a carbon nanomaterial-containing film 110 is formed on a substrate 100. Then, a photoresist 102 is formed on the carbon nanomaterial-containing film 110, and the photoresist 102 is exposed through a photomask 104 (FIG. 1(B)). The exposed photoresist 102 is developed to obtain a resist mask 106 corresponding to the pattern of the photomask 104 (FIG. 1(C)). After this, the substrate 100 on which the carbon nanomaterial-containing film 110 and the resist mask 106 are formed is immersed in the etchant 108 so that the carbon nanomaterial-containing film 110 comes into contact with the etchant 108 (FIG. 1(C)). In this state, the carbon nanomaterial-containing film 110 exposed from the resist mask 106 is irradiated with light, and the carbon nanomaterial-containing film 110 is partially oxidatively decomposed. Subsequently, the resist mask 106 is removed, so that the carbon nanomaterial-containing film 110 that was covered by the resist mask 106 and was not oxidatively decomposed remains on the substrate 100, forming a patterned carbon nanomaterial film 112 (FIG. 1(D)). Through the above series of processes, the carbon nanomaterial-containing film 110 having a shape corresponding to the arrangement pattern of the resist mask 106 can be formed on the substrate 100. This series of processes will be described in detail below.

[0015] 2. Substrate There are no particular limitations on the material contained in the substrate 100, and it may be a semiconductor such as silicon or germanium, a compound semiconductor such as gallium nitride, indium phosphide, or cadmium telluride, a ceramic such as alumina, sapphire, or zirconium oxide, a silicon oxide such as glass or quartz, or a polymer such as polyimide or polycarbonate. The substrate may be flexible. Typical examples include a single crystal silicon substrate, a glass substrate, a sapphire substrate, and a quartz substrate.

[0016] 3. Carbon nanomaterial-containing film Carbon nanomaterials include carbon nanotubes, graphene, and fullerenes.

[0017] When carbon nanotubes are used as the carbon nanomaterial, there is no restriction on their structure, and they may be single-walled or multi-walled carbon nanotubes. The carbon nanotubes may have capped ends, or may have a structure in which one or both ends are open. Therefore, carbon nanomaterials called carbon nanohorns may also be used in this processing method. Peapods, which are carbon nanotubes that contain fullerenes, may also be used. There is no restriction on the length of the carbon nanotubes.

[0018] When graphene is used as the carbon nanomaterial, the carbon nanomaterial-containing film 110 may be a single-layer film of graphene, or may be a film containing oligographene, nanographene, graphene oxide, or graphite, in which a plurality of graphenes are stacked. In addition, a part of the basic skeleton of graphene may be oxidized.

[0019] When fullerene is used as the carbon nanomaterial, C 60 Or C 70 Not only that, but C 74 , C 76 , C 78 Alternatively, fullerenes containing metal ions such as scandium, lanthanum, and cerium may be used, or fullerenes in which some of the carbon has been modified and which have functional groups such as ester groups may be used.

[0020] The carbon nanomaterial-containing film 110 can be formed by appropriately selecting a known method. For example, a dispersion liquid containing a carbon nanomaterial is prepared, and the suspension is applied to the substrate 100 by applying a wet film formation method such as a spin coating method, a dip coating method, or a printing method, and then the solvent is evaporated to form the carbon nanomaterial-containing film 110. The solvent of the dispersion liquid may be water, or an organic solvent selected from carbonates, ethers, ketones, alcohols, hydrocarbons, halogen-containing hydrocarbons, esters, carboxylic acids, amines, amides, nitroalkanes, sulfur compounds, and the like may be used. A dispersant such as a surfactant may be added to the dispersion liquid. However, it is preferable to adjust the dispersion liquid so that no dispersant is used or the concentration of the dispersant is low so as not to affect the electrical properties of the carbon nanomaterial-containing film 110 after patterning.

[0021] Alternatively, a catalyst for producing carbon nanotubes or graphene may be fixed on the substrate 100, and carbon nanotubes or graphene may be grown from the surface of the substrate 100. Specifically, a catalyst layer containing a metal such as iron, cobalt, nickel, or copper is formed on the substrate 100 using a vacuum deposition method, a metal organic chemical vapor deposition (MOCVD) method, a sputtering method, or the like. If necessary, the catalyst layer may be heat-treated in the presence of a reducing gas such as hydrogen. Alternatively, a dispersion liquid containing fine particles of a metal may be applied to the substrate 100 to form a catalyst layer. Then, carbon nanotubes or graphene are grown using a thermal CVD method. For example, the substrate 100 is heated at a temperature of 600° C. to 1200° C. in the presence of a raw material gas such as benzene, acetylene, carbon monoxide, methane, or ethanol. When a plasma CVD method is used instead of the thermal CVD method, heating may be performed at a temperature of 400° C. to 600° C. As a result, carbon nanotubes or graphene grow from the catalyst as a base point, and a carbon nanomaterial-containing film 110 can be formed on the substrate 100.

[0022] When graphene is used, the carbon nanomaterial-containing film 110 may be formed by reducing graphene oxide on the substrate 100. Specifically, graphite powder is oxidized using an oxidizing agent such as potassium permanganate, potassium dichromate, or hydrogen peroxide, and then the graphene oxide produced by the oxidation is dispersed in a solvent such as water to obtain a dispersion. This dispersion is applied onto the substrate 100 to form a film containing graphene oxide. Subsequently, the film containing graphene oxide is irradiated with light from a light source such as a mercury lamp in the atmosphere. Oxygen in the graphene oxide is released by the light irradiation, and the carbon nanomaterial-containing film 110 containing graphene is formed on the substrate 100.

[0023] Alternatively, the substrate 100 may be bonded onto the carbon nanomaterial-containing film 110 formed on another support substrate, and the carbon nanomaterial-containing film 110 may be transferred from the support substrate to the substrate 100. For example, a support substrate having a thin film containing a metal such as iron, cobalt, nickel, or copper formed on its surface is used, and a CVD method is applied to grow carbon nanotubes or graphene using the metal as a catalyst. Then, the film containing carbon nanotubes or graphene is coated with a film containing a polymer such as polymethylmethacrylate, poly(ethylene terephthalate), or polyimide. After this, the substrate 100 is bonded via the polymer film, and the thin film containing the metal is chemically removed with an iron chloride solution or the like, whereby the carbon nanomaterial-containing film 110 containing carbon nanotubes or graphene is transferred from the support substrate to the substrate 100.

[0024] 4. Preparation of Resist Mask The resist mask 106 can also be prepared by applying known methods and materials. Specifically, the photoresist 102 is applied onto the substrate 100 on which the carbon nanomaterial-containing film 110 has been formed, using a wet film formation method, and the solvent is evaporated. Alternatively, the photoresist 102 may be formed by placing a solid resist film on the substrate 100 on which the carbon nanomaterial-containing film 110 has been formed. As will be described later, in this processing method, the carbon nanomaterial-containing film 110 is irradiated with light during etching. Therefore, it is preferable to use a negative photoresist so that the resist mask 106 is not solubilized by light irradiation during etching.

[0025] Thereafter, a photomask 104 having light-transmitting portions 104a and light-shielding portions 104b formed in a desired pattern is placed on the photoresist 102, and the photoresist 102 is exposed through the photomask 104 (FIG. 1(B)). The photoresist 102 is subsequently developed using an etchant such as an alkaline aqueous solution to obtain a patterned photoresist 102, i.e., a resist mask 106 (FIG. 1(C)). Note that FIG. 1(C) shows an example in which a negative photoresist 102 is used, and a resist mask 106 is formed in an area corresponding to the light-transmitting portions 104a. Although not shown, a stepper (reduced projection exposure device) or a direct drawing device may be used as the exposure device. In the former, light from a light source that has passed through the photomask 104 is collected by a projection lens, and the collected light is irradiated onto the photoresist 102. In the latter, the photomask 104 is not used, and laser light is directly irradiated onto the photoresist 102.

[0026] Alternatively, a metal mask containing a metal may be used instead of the resist mask 106 or together with the resist mask 106. For example, as shown in FIG. 10(A), a deposition mask 122 having openings 122a is placed on the substrate 100 on which the carbon nanomaterial-containing film 110 is formed. Then, the metal is heated and vaporized under high vacuum. As a result, the metal vapor is deposited and solidified on the carbon nanomaterial-containing film 110 through the openings 122a, and a metal mask 124 reflecting the pattern of the openings 122a is obtained (FIG. 10(B)). The metal used here may be any metal that is resistant to an oxidizing agent contained in an etchant used for etching the carbon nanomaterial-containing film 110 described later, and examples of the metal include gold and platinum.

[0027] Alternatively, the metal mask 124 may be formed by using the resist mask 106 prepared by the above-mentioned process without using the deposition mask 122 having the openings 122a. That is, as shown in FIG. 11(A), a metal film 126 is formed by deposition on the carbon nanomaterial-containing film 110 on which the resist mask 106 is formed. Thereafter, the resist mask 106 is removed by heating or an organic solvent, and a patterned metal mask 124 containing a metal such as gold can be formed (FIG. 11(B)). In this case, the photoresist 102 may be either negative or positive.

[0028] 5. Etching of Carbon Nanomaterial-Containing Films After the resist mask 106 is formed, the carbon nanomaterial-containing film 110 is etched. The etching is performed by irradiating the carbon nanomaterial-containing film 110 with light in the presence of an etchant. More specifically, the substrate 100 on which the carbon nanomaterial-containing film 110 and the resist mask 106 are formed is placed in a container 120 containing an etchant 108 containing an oxidizing agent, and the carbon nanomaterial-containing film 110 is immersed in the etchant 108. In this state, the carbon nanomaterial-containing film 110 is irradiated with light (FIG. 1(C)). The light may be irradiated from the upper surface of the substrate 100 (the surface on which the carbon nanomaterial-containing film 110 is formed), but if the irradiated light passes through the substrate 100, it may be irradiated from the lower surface opposite to the upper surface.

[0029] Examples of oxidizing agents contained in the etchant include chlorine-based oxoacids such as hypochlorous acid, chlorous acid, and chloric acid, and their salts, ozone, hydrogen peroxide, metal permanganates such as potassium permanganate, metal chromates such as potassium chromate and potassium dichromate, and halogens such as chlorine, iodine, and bromine. Among these, chlorine-based oxoacids or their metal salts that have high oxidizing power, are easy to dispose of, and are rapidly decomposed by light are preferred. A typical example of a chlorine-based oxoacid is hypochlorous acid, and examples of its metal salts include sodium hypochlorite, potassium hypochlorite, and calcium hypochlorite.

[0030] The solvent constituting the etchant may be any solvent that sufficiently dissolves the oxidizing agent, and water, which is inexpensive and non-toxic, is a typical example. In addition to water, the etchant may contain an organic solvent that is highly hydrophilic and does not swell the resist mask 106. For example, the etchant may contain an alcohol-based solvent such as ethanol or isopropanol, a ketone-based solvent such as acetone or methyl ethyl ketone, or an amide-based solvent such as N,N-dimethylformamide or N,N-dimethylacetamide. The concentration of the oxidizing agent in the etchant depends on the type and thickness of the carbon nanomaterial contained in the carbon nanomaterial-containing film 110, but can be selected from a range of, for example, 1% by weight to 25% by weight or 1% by weight to 20% by weight. By selecting the oxidizing agent concentration within this range, a sufficient etching rate can be obtained and the oxidizing agent remaining after etching can be easily removed.

[0031] The etchant 108 may further contain a surfactant. There is no restriction on the type of surfactant, and it may be an ionic surfactant or a nonionic surfactant. Examples of the former include saturated or unsaturated aliphatic carboxylates, alkyl sulfates, polyoxyethylene sulfates, alkylbenzene sulfonates, alkyl phosphates, tetraalkylammonium salts, trialkylamine oxides, and betaines having an ammonium cation and a carboxylate anion. Examples of the latter include polyoxyethylene alkyl ethers, fatty acid sorbitan esters, alkyl polyglucosides, fatty acid diethanolamides, and alkyl monoglyceryl ethers. There is no restriction on the concentration of the surfactant in the etchant 108, and it may be selected from a range of, for example, 0.1% by weight or more and 10% by weight or less. By selecting the concentration of the surfactant from the above concentration range, etching can be accelerated, foaming during etching can be suppressed, and the surfactant can be easily removed by washing after etching.

[0032] The light source used for the light irradiation may be any light source capable of irradiating light corresponding to the absorption wavelength of the oxidizing agent. By selecting the light source in this way, the oxidizing agent in the etchant is photoexcited. For example, when hypochlorous acid or sodium hypochlorite is used as the oxidizing agent, the absorption wavelength of these oxidizing agents is present in the range of 200 nm to 400 nm, so a light source that emits light of a wavelength selected from this wavelength range may be used. Preferably, a light source capable of covering the above absorption wavelength range is used. Specifically, the light source may be a xenon lamp (xenon short arc lamp), a halogen lamp, a high pressure mercury lamp, a deuterium lamp, a UV lamp (Xe / Hg far ultraviolet lamp), or the like.

[0033] Etching may be performed at room temperature (20°C to 25°C), under cooling (0°C or higher and room temperature or lower), or under heating (room temperature or higher and 100°C or lower). In order to prevent the temperature of the etchant 108 from increasing due to the light source, a cooling device (not shown) may be connected to the container 120 to maintain the temperature of the etchant 108 constant while etching. Although not shown, a stirring mechanism may be provided in the container 120 to stir the etchant 108 while etching. The etching time may be determined in consideration of the type and thickness of the carbon nanomaterial contained in the carbon nanomaterial-containing film 110, and may be selected from the range of, for example, 5 seconds to 30 minutes, 1 minute to 30 minutes, or 5 minutes to 20 minutes.

[0034] After etching is completed, the substrate 100 is washed with a solvent such as water, alcohol, or ketone. The remaining resist mask 106 is then removed (FIG. 1(D)). To remove the resist mask 106, the substrate 100 may be treated with a known stripping solution. Examples of the stripping solution include an alkaline solution containing tetraalkylammonium hydroxide or amine, and an organic solvent such as N-methyl-2-pyrrolidone (NMP) or acetone. When the metal mask 124 is used, the metal mask 124 may be removed using an aqueous solution containing potassium iodide and iodine as an etchant.

[0035] The above process allows the carbon nanomaterial-containing film 110 patterned on the substrate 100 to be produced. In this processing method, the carbon nanomaterial-containing film 110 is processed by so-called wet etching using the etchant 108. Therefore, compared with processing methods using dry etching, this method has the advantage of being able to process a large number of substrates at once. As shown in the examples, a practical etching rate cannot be obtained using an etchant alone, whereas the etching rate of the carbon nanomaterial-containing film 110 is dramatically increased by irradiating light. Furthermore, in this processing method, it is not necessary to perform a preliminary treatment (such as film formation to promote etching) on ​​the carbon nanomaterial-containing film 110 prior to etching. This means that by applying the embodiment of the present invention, it is possible to provide a practical wet etching technique for functional thin films containing various carbon nanomaterials including not only carbon nanotubes but also graphene and fullerene. EXAMPLES

[0036] 1. Example 1 In this Example 1, the results of treating the carbon nanomaterial-containing film 110 with an etchant containing sodium hypochlorite as an oxidizing agent under light irradiation conditions will be described. In addition, in the following Examples 1 to 4, graphene was used as the carbon nanomaterial.

[0037] 1-1.Experiment A 1 cm x 1 cm single crystal silicon substrate (Sigma-Aldrich, hereinafter the same) on which single layer graphene was formed via a silicon oxide thin film was used as a sample. This sample was placed in a glass bottle, and 10 mL of a 0.05 g / mL aqueous solution of sodium hypochlorite (Wako Pure Chemical Industries, Ltd.) was added to the glass bottle. At room temperature, the surface of the single crystal silicon substrate on which graphene was formed was irradiated with light using a xenon lamp (Hamamatsu Photonics, model number LC5, 100 W, irradiation wavelength range 200 to 2000 nm, hereinafter the same).

[0038] 1-2.Results FIG. 2(A) shows an optical microscope photograph (Nano Search Microscope SFT-4500, manufactured by Shimadzu Access Co., Ltd.; the same applies below) of the sample before treatment with the sodium hypochlorite aqueous solution. FIG. 3(A) shows the Raman spectroscopy spectra measured at measurement points 1 to 4 in FIG. 2(A). The Raman spectroscopy spectra were obtained using a Renishaw inVia Raman spectrophotometer. As shown in FIG. 2(A), the graphene-containing film before treatment was observed as a nearly uniform film. Furthermore, as shown in FIG. 3(A), the D band (1345 cm ) specific to a graphene monolayer film was observed at each measurement point. -1 ), G band (1595cm -1 ), 2D band (2685cm -1 ) was observed, and no difference in the intensity of these peaks was observed between measurement points 1 and 4. These results indicate that the graphene-containing film forms a nearly uniform monolayer structure on the single crystal silicon substrate.

[0039] On the other hand, an optical microscope image of the sample taken 5 minutes after the start of the etching process under light irradiation (Fig. 2(B)) confirmed that many defects had formed in the graphene-containing film on the single crystal silicon substrate. As can be seen from the Raman spectroscopy spectra (Fig. 3(B)) at measurement points 1 to 4 shown in Fig. 2(B), almost no graphene-specific bands were observed in any of the spectra except for measurement point 4.

[0040] Furthermore, 20 minutes after the start of the etching process under light irradiation, the graphene-containing film could not be confirmed in the optical microscope image (Fig. 2(C)). In addition, the Raman spectroscopy measurement results for measurement points 1 to 4 shown in Fig. 2(C) showed that although a band specific to graphene was faintly detected at measurement point 1, the presence of graphene could not be confirmed at the other measurement points (Fig. 4(A)).

[0041] In contrast, when the sample was left in a sodium hypochlorite aqueous solution at 40°C for 120 minutes without light irradiation, it was confirmed by optical microscope observation that a graphene-containing film remained on the single crystal silicon substrate, as shown in Figure 2(D). Furthermore, the Raman spectroscopy measurements at measurement points 1 to 4 in Figure 2(D) confirmed that graphene clearly remained at measurement points 3 and 4 (Figure 4(B)).

[0042] The above results clearly show that light irradiation is extremely effective in accelerating the etching of films containing carbon nanomaterials, including graphene. Although the detailed mechanism is not yet clear, it is thought that the oxidizing agent excited by light decomposes to generate oxygen radicals. These oxygen radicals react with the sp 2 It is believed that the attack of carbon oxidizes the carbon nanomaterials, which increases their hydrophilicity and improves their solubility in the etchant. In addition to or instead of this mechanism, it is believed that a mechanism in which oxygen radicals cleave some of the carbon-carbon bonds, resulting in the oxidative decomposition of the carbon nanomaterials, also contributes.

[0043] 2. Example 2 In this Example 2, the results of investigating the effect of a surfactant on etching of a graphene-containing film will be described.

[0044] 2-1. Experiment A 6% by weight aqueous solution of sodium hypochlorite containing an alkylamine oxide surfactant (Kitchen Power Bleach, manufactured by Lion Hygiene Co., Ltd., the same applies below) was used as the etchant. A 1 cm x 1 cm single crystal silicon substrate on which single layer graphene was formed via a silicon oxide thin film was placed in a glass bottle, and the etchant was added to the glass bottle so that the sample was completely immersed in the etchant. After that, a xenon lamp was used to irradiate the surface of the single crystal silicon substrate on which graphene was formed at room temperature for 5 minutes.

[0045] 2-2.Results Optical microscope photographs of the sample before and after treatment with the etchant are shown in Figures 5(A) and 5(B), respectively. Raman spectroscopy spectra measured at measurement points 1 to 4 in Figures 5(A) and 5(B) are shown in Figures 6(A) and 6(B), respectively. Comparing Figures 5(A) and 5(B) shows that the graphene observed before treatment with the etchant is hardly observed after treatment. In addition, comparing Figures 6(A) and 6(B), the peaks of each band derived from graphene are clearly detected at all measurement points before treatment, but these peaks are not observed at any measurement points after treatment.

[0046] The sample with an etching time of 5 minutes in Example 1 corresponds to a comparative example for this Example (FIGS. 2(B) and 3(B)). Comparing FIG. 5(B) with FIG. 2(B), it can be confirmed that the graphene-containing film is removed more quickly by adding a surfactant. In addition, the result shown in FIG. 3(B) shows that graphene remains at some measurement points in the absence of a surfactant, whereas the result shown in FIG. 6(B) shows that no graphene remains at any measurement points when a surfactant is used. These results show that the etching rate is further improved by adding a surfactant.

[0047] 3. Example 3 In this example, a result of patterning a graphene-containing film including a single-layer graphene by etching using a resist mask will be described.

[0048] 3-1. Experiment This example was carried out according to the scheme shown in Figure 1. Specifically, a 1 cm x 1 cm single crystal silicon substrate on which single-layer graphene was formed via a silicon oxide thin film was used as a sample, and a UV resin (hard type) made by Padico Co., Ltd., containing an acrylic resin, was partially applied onto the graphene-containing film. This UV resin was irradiated with a UV lamp (manufactured by AS ONE Corporation, model number SLUV-8) for about 5 minutes to harden it, forming a resist mask.

[0049] Next, the sample with the resist mask formed was placed in a glass bottle, and an etchant was added to the glass bottle so that the sample was completely immersed. The etchant used was a 6 wt% sodium hypochlorite aqueous solution containing an alkylamine oxide surfactant. Then, a xenon lamp was used to irradiate the surface of the single crystal silicon substrate with the graphene formed thereon with light at room temperature for 5 minutes. Next, the sample was removed from the etchant, washed with water, and the resist mask was physically peeled off.

[0050] 3-2.Results Figure 7(A) shows an optical microscope photograph of the sample before the resist mask was prepared, and Figure 7(B) shows the intensity mapping data of the 2D band detected by the Raman spectroscopy spectrum of the area enclosed by the dotted square in Figure 7(A). From these figures, it was confirmed that the graphene-containing film on the single crystal silicon substrate had a nearly uniform thickness.

[0051] FIG. 8(A) is an optical microscope image of a sample obtained by etching a graphene-containing film on which a resist mask was formed and then peeling off the resist mask. In the figure, the belt-shaped region marked with the reference numeral 112 is the region where the resist mask was formed. As can be seen from FIG. 8(A), the graphene-containing film remains as a selectively patterned carbon nanomaterial film 112 in the region where the resist mask was formed, and the graphene-containing film has been removed from other regions. This is also confirmed by the 2D band intensity mapping data (FIG. 8(B)) detected by the Raman spectroscopy spectrum of the region surrounded by the dotted square in FIG. 8(A).

[0052] FIG. 9(A) shows a phase distribution image of the sample obtained using an AFM (Shimadzu Access Co., Ltd., Nano Search Microscope, Model No. SFT-4500), and FIG. 9(B) shows the height analysis result of the sample along the line AB in FIG. 9(A). As can be seen from FIG. 9(A) and FIG. 9(B), the region where the resist mask was formed (the strip region marked with the reference numeral 112 in FIG. 9(A)) is higher than the other regions where the resist mask was not formed. Specifically, as shown in FIG. 9(B), the measurement point 2 in the region where the resist mask was formed is higher than the measurement point 1 in the region where the resist mask was not formed. Similarly, the measurement point 4 in the region where the resist mask was formed is higher than the measurement point 3 in the region where the resist mask was not formed. The difference in height between the measurement points 2 and 4 and the measurement points 1 and 3 was 0.5 nm to 0.8 nm. These results also prove that the graphene-containing film is present in the region where the resist mask was formed.

[0053] 4. Example 4 In this example, an example will be described in which a graphene-containing film including a single-layer graphene is patterned by etching using a metal mask.

[0054] 4-1. Experiment A 1 cm x 1 cm single crystal silicon substrate on which single-layer graphene was formed via a silicon oxide thin film was used as a sample. A metal mask was formed by evaporating a thin gold film (100 nm thick) onto this graphene-containing film via a deposition mask or resist mask. Two types of metal masks with different patterns (metal masks A and B) were used here. Hereinafter, the samples using metal masks A and B will be referred to as samples A and B, respectively. Optical microscope photographs of samples A and B on which metal masks were formed are shown in Figures 12(A) and 13(A), respectively. From these figures, it can be seen that a patterned thin gold film was formed as a metal mask in the area marked with the reference numeral 106.

[0055] Next, samples A and B with the metal masks formed were placed in glass bottles, and etchant was added to the bottles so that the samples were completely immersed. The etchant used was a 6 wt% aqueous solution of sodium hypochlorite containing an alkylamine oxide surfactant. Then, a xenon lamp was used to irradiate the surface of the single crystal silicon substrate with the graphene formed thereon with light at room temperature for 5 minutes. Next, the samples were removed from the etchant and washed with water, and the metal masks were peeled off with an aqueous solution of potassium iodide and iodine.

[0056] The left figure in Figure 12(B) is an optical microscope image of sample A after the metal mask was peeled off, and the right figure is 2D band intensity mapping data detected by Raman spectroscopy of the area surrounded by the dotted rectangle in the left figure. As can be seen from the optical microscope image in Figure 12(B), the presence of single-layer graphene can be clearly confirmed in the area where the metal mask was formed. The mapping data also shows that single-layer graphene remains in the above area, whereas single-layer graphene has disappeared in the area exposed from the metal mask.

[0057] The same thing was confirmed for sample B. Specifically, as shown in Fig. 13(B) and an enlarged view of a part of it (enclosed in the dotted rectangle) (left side of Fig. 13(C)), it was confirmed by optical microscope observation that single-layer graphene remained in the area where the metal mask was formed. In addition, the 2D band intensity mapping data (right side of Fig. 13(C)) detected by Raman spectroscopy spectrum of the area enclosed in the dotted rectangle in Fig. 13(C) shows that single-layer graphene exists in the above area, whereas single-layer graphene does not exist in the area exposed from the metal mask.

[0058] From the above, it was confirmed that the graphene-containing film formed on a substrate can be wet-etched by applying the processing method according to one embodiment of the present invention. This result indicates that the processing method can contribute as a new means for providing electronic devices containing carbon nanomaterials as conductive members. [Explanation of symbols]

[0059] 100: substrate, 102: photoresist, 104: photomask, 104a: light-transmitting portion, 104b: light-shielding portion, 106: resist mask, 108: etchant, 110: carbon nanomaterial-containing film, 112: patterned carbon nanomaterial film, 120: container, 122: deposition mask, 124: metal mask, 126: metal film

Claims

1. forming a resist mask and / or a metal mask on a carbon nanomaterial-containing film on a substrate; Irradiating the carbon nanomaterial-containing film with light in the presence of an etchant containing an oxidizing agent; and removing the resist mask and / or the metal mask; A method for processing a carbon nanomaterial-containing film, wherein the light used in the light irradiation contains light having a wavelength selected from the range of 200 nm or more and 400 nm or less.

2. forming a resist mask and / or a metal mask on a carbon nanomaterial-containing film on a substrate; Irradiating the carbon nanomaterial-containing film with light in the presence of an etchant containing an oxidizing agent; and removing the resist mask and / or the metal mask; The method for processing a carbon nanomaterial-containing film, wherein the metal mask comprises gold or platinum.

3. forming a resist mask and / or a metal mask on a carbon nanomaterial-containing film on a substrate; Irradiating the carbon nanomaterial-containing film with light in the presence of an etchant containing an oxidizing agent and a surfactant; and A method for processing a carbon nanomaterial-containing film, comprising removing the resist mask and / or the metal mask.

4. The method of claim 1 , wherein the carbon nanomaterial is a carbon nanotube, a graphene, or a fullerene.

5. The method according to claim 1 , wherein the carbon nanomaterial-containing film is a single layer of graphene or a laminated film of graphene.

6. 4. The method according to claim 1, wherein the oxidizing agent is selected from hypochlorous acid and sodium hypochlorite.

7. The method according to claim 1 , wherein the light irradiation is performed so as to excite the oxidizing agent.

8. The method according to claim 1 , wherein the concentration of the oxidizing agent in the etchant is 1% by weight or more and 25% by weight or less.

9. The method according to claim 1 , wherein the forming of the resist mask is performed using a negative photoresist.

10. The method according to claim 1 , wherein the light irradiation is performed in a state where the carbon nanomaterial-containing film is immersed in the etchant.

11. The method of claim 3 , wherein the surfactant is an ionic surfactant.

12. The method of claim 11 , wherein the concentration of the surfactant in the etchant is from 0.01% to 10% by weight.

Citation Information

Patent Citations

  • Promoted oxidation process

    JP2009101302A

  • Method for production of hypochlorous acid water

    JP2011111386A

  • Method for patterning non metal conductive layer

    JP2013225649A

  • Patterned aromatic carbon film and method for manufacturing the same

    JP2014172792A